Yes, We Can! : um estudo sobre desemprenho em times de vendas - Monteiro, Rodrigo Bastos (2015)
Working in teams and its role in individual performance is the subject of this dissertation. We tried to identify if two team beliefs had an impact on the performance of salespersons: team potency and quality of interpersonal climate. It was hypothesized that team potency increases self-efficacy and adaptability of the salesperson. Also, the quality of interpersonal climate would moderate these relationships, increasing. Finally, the self-efficacy and adaptability of the salesperson would have positive impact on sales performance. To test the hypotheses made up a data collection from the 290 sellers in 101 teams sales a manufacturer of filters and filter elements of water. The sample showed rates of validity and reliability suitable. Using the IBM® SPSS® Statistics version 21, were built 8 regression models tested the hypothesis that with the dependent and independent variables of the study, more covariates. The results showed that team aspects impact on the performance of the salesperson. Team potency has positive relationship with self-efficacy and adaptability of the salesperson. Self-efficacy and adaptability of the salesperson has a positive impact on the sales performance of the seller. The quality of interpersonal climate, differently to the proposal of the conceptual model of this work, had no moderating relationship in team potency on individual aspects. On the contrary, showed antecedent condition for adaptability and self-efficacy, and impact on sales performance. Additionally we tested and found positive and significant results of mediation adaptability and self-efficacy between team potency and salesperson performance and quality of the interpersonal climate and salesperson performance. The results of the work are discussed, the limitations are identified and future research suggestions appear.